Revitalisasi Cagar Budaya Makam Pahlawan Nasional Teuku Umar Johan Pahlawan sebagai Bentuk Keberlanjutan Ekologis - Amri Wahid Hidayat; Tri Quari Handayani; Akmal Saputra; Yeni Sri Lestari; Saiful Asra; Cut Irna Liyana; Aulia Risky; Samwil Samwil; Lilis Sariyanti; Devi Intan Chadijah (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2026)
The Community Service Activity (PkM) is an integral part of the implementation of the Tri Dharma of Higher Education, which aims to apply academic knowledge for the welfare of society. This PkM was conducted on May 21, 2025, at the Cultural Heritage Site of the National Hero Teuku Umar’s Tomb in West Aceh, as part of the 10th National Sociology Conference attended by sociology lecturers from various universities across Indonesia. The program aimed to preserve the historical site while strengthening the social and ecological values of the surrounding community through environmental revitalization and tree planting activities. The approach used was a problem-solving method with stages of preparation, implementation, and evaluation. The results showed improvements in environmental cleanliness and aesthetics, as well as active community participation in preserving the site. Beyond ecological benefits, the activity fostered social cohesion and collective awareness of cultural heritage preservation. Academically, this PkM serves as tangible evidence of the Tri Dharma implementation and demonstrates sociology’s practical contribution in addressing social challenges and supporting sustainable local development.